COLLABORATIVE WRITING TECNIQUE EFFECT ON THE STUDENTS’ WRITING ACHIEVEMENT - Desi Afifah (Language-Edu, 2020)
The aim of the research is to know the significant effect of collaborative writing about the achievement of students’ writing recount text. This research was conducted to investigate the significant effect of CWT on the students’ achievement in writing recount text is effective. The hypothesis is there is significant effect of CWT on students’ achievement in writing recount text. This research is an experimental study and uses quasi experimental research design. The research subject is the students of one of second grade of state junior high school in Karangploso. This study used two groups of students, experimental and control group. Testing writing composition was used as the data collection technique and t-Test calculated by SPSS Statistic 20 was used as the data analyze technique to discover the difference between students’ pretest and posttest score of control and experimental group. The significant (2-tailed) score of posttest control and experimental group is lower than 0.05 % that is 0,001. It indicates that the result of posttest of experimental and control group were different. Then, that CWT in teaching writing of recount text is effective as the hypothesis is accepted